Settlement of Criminal Cases of Children as Perpetrators of Sexual Harassment Based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System - Made Sukereni (Fakultas Hukum, Universitas Warmadewa, 2022)
Nowadays, crimes involving children are very common. One of them is sexual abuse by children. The purpose of this study is to find out (1) the settlement of criminal cases of children as perpetrators of sexual harassment based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA); and (2) criminal sanctions for children who commit sexual abuse in accordance with the concept of the SPPA Law. The research method used is a type of normative legal research. The results of the study show (1) that the settlement of criminal cases of children as perpetrators of sexual abuse based on the SPPA Law can be carried out in 2 (two) ways, namely through litigation or trial and also through diversion or mediation, which are useful for providing opportunities for a child to improve himself. ; and (2) criminal sanctions for children who commit sexual abuse in accordance with the concept of the SPPA Law can be in the form of imprisonment and can also be action sanctions. The reason is, in the event that a child commits a criminal act of obscenity, diversion cannot be sought if the criminal penalty is more than 7 years. Nevertheless, the judge in deciding the case of criminal sanctions against the crime of sexual abuse by children must still pay attention to the mental state and rights of the child, namely by providing sanctions in the form of actions as regulated in Article 82 paragraph (1) of the SPPA Law.able to be applied properly and appropriately by students and parties involved in it.